2006
DOI: 10.1038/sj.embor.7400852
|View full text |Cite
|
Sign up to set email alerts
|

The protein kinase TOUSLED is required for maintenance of transcriptional gene silencing in Arabidopsis

Abstract: TOUSLED-like kinases (TLKs) are highly conserved in plants and animals, but direct evidence linking TLKs and transcriptional gene silencing is lacking. We isolated two new alleles of TOUSLED (TSL). Mutations of TSL in ros1 reactivate the transcriptionally silent 35S-NPTII transgene and the transcriptionally silent endogenous loci TSI (TRANSCRIPTIONAL SILENCING INFOR-MATION). Chromatin immunoprecipitation (ChIP) analysis shows that histone H3Lys9 dimethylation is decreased in the reactivated transgene and endog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 31 publications
4
58
1
Order By: Relevance
“…In addition, as mentioned earlier, in Arabidopsis, ASF1B is phosphorylated by the TOUSLED protein kinase (Ehsan et al, 2004). Arabidopsis tls mutants are highly sensitive to genotoxic stress, including UV-B radiation (Wang et al, 2007). Even more, in humans, Sen and De Benedetti (2006) provided evidence that TLK1B protects against UV radiation via Asf1-mediated chromatin assembly at the sites of UV damage.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, as mentioned earlier, in Arabidopsis, ASF1B is phosphorylated by the TOUSLED protein kinase (Ehsan et al, 2004). Arabidopsis tls mutants are highly sensitive to genotoxic stress, including UV-B radiation (Wang et al, 2007). Even more, in humans, Sen and De Benedetti (2006) provided evidence that TLK1B protects against UV radiation via Asf1-mediated chromatin assembly at the sites of UV damage.…”
Section: Discussionmentioning
confidence: 98%
“…This suggests possible regulatory interactions involving these genes that require BRM-mediated chromatin remodelling. TSL was recently shown to be involved in chromatin modiWcations (Wang et al 2007). Interestingly, the BRAHMA SWI/SNF CRC in Drosophila melanogaster was found to act together with a histone chaperone ASF1, which is a target for a TSL-like kinase (Moshkin et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…of the core DNA-replication proteins, including the DNA single-strand-binding protein RPA2A (Xia et al, 2006), Pola (Liu et al, 2010a), Pol « (Yin et al, 2009), POLD2 (this study), RFC1 (Liu et al, 2010b), and TOUSLED protein kinase (Wang et al, 2007). Other studies have identified other DNA replication-related proteins involved in mediating TGS, including BRU1 (Takeda et al, 2004), chromatin assembly factor (CAF-1) subunits FAS1 and FAS2 (Ono et al, 2006;Schonrock et al, 2006), and TEBICHI (Inagaki et al, 2009).…”
Section: Discussionmentioning
confidence: 99%